Evolution of ideas about pathological mineralization in soft tissues (literature review). - Moskalenko, R. A.; Romanіuk A. M. (Морфологія / Morphologia / Morfologìâ, 2016)
Ectopic deposition of calcium compounds in the human body is represented by salts of calcium phosphate, mainly by hydroxyapatite. The formation of stones in the urinary system is the exception, there calcium oxalate and phosphate octacalcium are formed. As pathological biomineralization are presented by calcium compounds, the term "ectopic calcification" can be considered as identical or very similar in the meaning. Ectopic calcification is defined as unnatural mineralization of soft tissue of a living organism. Basing on the fact, that pathologic biomineralization is the result of cells and tissues damage, diseases, aging and systemic metabolic disorders, this process was viewed as degenerative and passive. This approach had dived pathological calcification into dystrophic and metastatic, and in native science also metabolic is marked out. Many recently opened specific regulatory calcification mechanisms of soft tissues indicate an activity of this process and its similarity to the processes of ossification of the skeletal system. A whole amount of new observations and researches convinces that the process of calcium compounds depositing in soft tissues are regulated and evolutionarily caused by compensatory and adaptive process. The concentration of calcium and phosphates in the extracellular fluid is close to that, which is necessary for the spontaneous formation of calcium phosphate crystals. Precipitation of minerals is prevented by inhibiting factors, the number of which is at enough basic level. Thus, ectopic biomineralization can be encouraged not only by activating factors increase, but also by an inhibitory factors decrease. Thus, various forms of pathological biomineralization can be caused by: 1) only activating factor increase 2) only decrease or loss of mineralization inhibitors, 3) a combination of violations of mineral formation activation and inhibition.